Arctic mineral futures: tracing geoscience knowledge from field to community in the Northwest Territories, Canada - Becker, M (2022)
This thesis explores the ‘becoming’ of mineral resources in the Northwest Territories (NWT), Canada, and the role that geoscience knowledge and bodily-material relations play in that process. Mineral resources are assembled through a diversity of practices and knowledges which enable their identification, bounding and circulation within global economies. Existing literatures have explored the circulation, valuation and demands for commodities largely from a cultural perspective. In response, this thesis presents another approach which focusses on the relations between geological materials and the bodies and emotions of scientists and citizens. This is done by drawing on literatures from cultural and resource geographies and science and technology studies.